Effects of Malondialdehyde on Growth Performance, Gastrointestinal Health, and Muscle Quality of Striped Catfish (Pangasianodon hypophthalmus) - Cong Peng; Xinlangji Fu; Yumeng Zhang; Haitao Zhang; Yuantu Ye; Junming Deng; Beiping Tan (Antioxidants)
Malondialdehyde (MDA) is a reactive carbonyl compound produced through lipid peroxidation during feed storage, which poses a significant threat to fish health. This study aimed to evaluate the effects of dietary MDA on the growth rate, gastrointestinal health, and muscle quality of striped catfish (Pangasianodon hypophthalmus). A basal diet (M0) containing 34% crude protein and 10.5% crude lipid was formulated. Each group was sprayed with malondialdehyde solution (0, 5, 10, 20, 40, and 80 mg/kg, on dietary crude lipid basis; 0, 0.53, 1.07, 2.13, 4.26, and 8.52 mg/kg, on dietary basis) before feeding, respectively. Each diet was randomly assigned to triplicates of 30 striped catfish (initial weight 31.38 g) per net cage. After 8 weeks, dietary inclusion of MDA regardless of level significantly depressed the growth rate and feed utilization. The extent of structural damage to the gastrointestinal tract increased progressively with increasing dietary MDA levels. The extent of damage to the intestinal biological barrier (intestinal microbial structure), chemical barrier (trypsin, lipase, amylase, and maltase activity), physical barrier (zonula occludent-2, occludin, claudin 7α, and claudin 12 relative expression), and immune barrier (contents of complement 4, complement 3, immunoglobulin M, and lysozyme activity) was dose-related to dietary MDA. Moreover, a linear decline in the activities of intestinal antioxidant enzymes (catalas, superoxide dismutase, et al.) and anti-inflammatory factor (transforming growth factor beta1, interleukin 10) relative expression was noted alongside an increase in dietary MDA content. In contrast, the relative expression levels of intestinal inflammatory factor (interleukin 8, transcription factor p65, tumor necrosis factor alpha) relative expression displayed an opposing trend. Additionally, dietary MDA exerted a linear influence on muscle color and texture characteristics. In conclusion, high doses of MDA (5–80 mg/kg) reduced the growth performance of striped catfish, attributed to linear damage to the gastrointestinal tract, a linear decrease in antioxidant function, and the occurrence of an inflammatory response. High doses of MDA (>40 mg/kg) were observed to significantly increase dorsal muscle b-value and induce muscle yellowing.